Alcoholism and Conditional Reasoning: Difficulties in Specific Mental Domains or in the General Use of Heuristics? - Miguel López Astorga (Psychologica Belgica, 2013)
A recent study states that alcoholics manifest conditional reasoning problems in certain specific mental domains, particularly in the domain of social interactions and in the domain in charge of precautions in hazardous situations. Nonetheless, given that the existence of such domains is questioned in different papers, a reinterpretation of the results of said study, in the light of a theoretical framework more widely accepted, might be needed. That is the aim of this paper, which will be based mainly on the dual-process theory and which will offer a critical review of both the Social contracts theory and the hazard management theory.